Bridging the gap: Enhancing pharmacist-physiscian collaboration through the provision of comprehensive medication reviews in community pharmacy - Ana I. Sanchez-Molina; Shalom I. Benrimoj; Ramon Ferri-Garcia; Fernando Martinez-Martinez; Miguel Angel Gastelurrutia; Noelia Amador-Fernandez; Victoria Garcia-Cardenas (Exploratory Research in Clinical and Social Pharmacy)
Background: Collaborative practice between physicians and pharmacists is particularly important in the provision of pharmacy services, such as Comprehensive Medication Reviews (CMR), which often require a close coordination between these professionals. Understanding the level and nature of this collaboration can assist in the development of strategies to enhance integrated care. Objectives: (1) To evaluate the changes in level of collaborative practice between community pharmacists and physicians in the context of a CMR service compared to usual practice, from the perspective of community pharmacists, and (2) to explore the determinants of such collaborative practice. Design: This research was conducted alongside a 12-months prospective longitudinal observational study. Methods: Community pharmacists providing CMR and pharmacists providing usual care (nCMR) from six provinces in Spain participated in the study. To measure the level of collaborative practice from the perspective of the community pharmacist, a previously validated tool was used. Collaborative practice was assessed at baseline, 6 months and 12 months. A multiple regression analysis was undertaken. Results: 323 pharmacists participated in the study. At the 12-month time point there were statistical differences between CMR and nCMR groups for all factors considered in the level of collaborative practice. Determinants which showed positive significant differences between groups included: rural location of the pharmacy, pharmacists being a pharmacy owner, and female gender of the physician. The age of the pharmacist was negatively associated with higher levels of collaborative practice. Conclusion: The study provides novel evidence on the level and nature of the collaborative practice between community pharmacists and physicians.